UPAYA MENINGKATKAN HASIL BELAJAR KELAS III PELAJARAN MATEMATIKA PADA MATERI BANGUN RUANG MELALUI MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) SDN 1 SRIBAWONO - Yuliawati, Lina; Misrodin; Pixyoriza (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mathematics learning in Grade III at SDN 1 Sribawono still shows low student learning mastery because the learning process is still teacher-centered, causing students to experience difficulties in understanding the material being taught. Therefore, this study aims to improve mathematics learning outcomes on plane geometry material through the implementation of the Contextual Teaching and Learning (CTL) model. This research employed the Classroom Action Research (CAR) method, which was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects of the study were 20 third-grade students of SDN 1 Sribawono. Data collection techniques included observation, interviews, learning achievement tests, and documentation. The results of the study showed an improvement in students’ learning outcomes in each cycle. The initial data obtained from the students’ daily test scores showed that only 30% of the students achieved mastery learning. This then increased in Cycle I, where 45% of the students achieved mastery learning. In Cycle II, the students’ test scores showed a significant improvement, reaching 90% mastery learning. Based on these findings, it can be concluded that the implementation of the CTL model was able to improve students’ mathematics learning outcomes on solid geometry material in Grade III at SDN 1 Sribawono.